Broadband Diffusion in Rural Maine: A Qualitative Assessment of Residents’ Attitudes - Simeone, Micaela (Maine Policy Review, 2024)
The transition to universal broadband in rural Maine will be transformative, and as policymakers shift focus towards adoption and use, they should thoroughly understand how rural Mainers view the internet more broadly and how they see broadband affecting their lives and communities. Through in-depth interviews with 27 Mainers across 8 counties, this project aims to document how rural Mainers are reacting to the inevitability of broadband penetration, what people view as the pros and cons of new digital infrastructure, what reasons people have for resistance or skepticism, and, in general, how the broadband conversation relates more broadly to people’s visions for the future of rural Maine.
Keywords: digital equity; meaningful broadband adoption